2015
DOI: 10.1016/j.rbr.2014.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Leptina e adiponectina no lúpus eritematoso sistêmico: correlações clínicas e laboratoriais

Abstract: Patients with SLE had elevated leptin levels, with association with renal involvement. Leptin and adiponectin were not correlated with disease activity. Low levels of leptin have been associated with the presence of LA and aCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…The inverse correlation between leptin and disease activity as observed in our study might be somewhat intriguing since leptin is assumed to be a strong pro-inflammatory agent increasing the synthesis of pro-inflammatory cytokines such as IL-6, IL-12 and TNF-α [6, 811, 13]. In fact, in the literature there are some data on a strong positive correlation between leptin levels and disease activity in other rheumatic diseases, including SLE [4, 4952, 58], RA [53, 75–77] and ankylosing spondylitis (AS) [64, 78], but to date the clinical significance of this elevation remains unknown. It is thought that serum leptin levels may be either a contributing factor or a marker of disease activity [14, 49, 54].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The inverse correlation between leptin and disease activity as observed in our study might be somewhat intriguing since leptin is assumed to be a strong pro-inflammatory agent increasing the synthesis of pro-inflammatory cytokines such as IL-6, IL-12 and TNF-α [6, 811, 13]. In fact, in the literature there are some data on a strong positive correlation between leptin levels and disease activity in other rheumatic diseases, including SLE [4, 4952, 58], RA [53, 75–77] and ankylosing spondylitis (AS) [64, 78], but to date the clinical significance of this elevation remains unknown. It is thought that serum leptin levels may be either a contributing factor or a marker of disease activity [14, 49, 54].…”
Section: Discussionmentioning
confidence: 56%
“…Particularly, the role of leptin as a potent pro-inflammatory agent has been investigated in spontaneous models of autoimmunity and studies in humans have further delineated the role of leptin in the pathogenesis of autoimmune diseases such as diabetes, inflammatory bowel disease, Behçet’s disease, systemic lupus erythematosus (SLE), and rheumatoid arthritis (RA) [35, 14, 18, 4854]. Adiponectin, another active hormone released by adipocytes, seems to be an attractive opposite in the field of autoimmune diseases, since it is considered to act as an anti-inflammatory molecule, and recently some studies demonstrated that plasma levels of adiponectin in patients with autoimmune diseases might be related to inflammatory status in their pathogenesis [2, 6, 52, 5557].…”
Section: Discussionmentioning
confidence: 99%
“…Leptin exerts its biological actions through the activation of leptin receptor, which belongs to the class 1 cytokine receptor superfamily and are encoded by the diabetes (db) gene . Numerous studies have shown abnormal increase in serum/plasma leptin levels in patients with SLE , but the data regarding association between leptin‐related gene polymorphisms and SLE is still very limited. Afroze et al .…”
Section: Introductionmentioning
confidence: 99%
“…5,6 Adiponectin may improve metabolic disorders, including those associated with SLE, due to these anti-inflammatory properties. Higher levels of circulating adiponectin in SLE patients correlate positively with inflammatory markers, 7 and SLE patients are reported to have higher serum adiponectin than healthy controls, while SLE patients with renal dysfunction are reported to exhibit higher serum levels than SLE patients without renal dysfunction. 8 Several studies reports elevated values of leptin and adiponectin in SLE patients.…”
Section: Introductionmentioning
confidence: 99%